ACTIVE TECTONICS OF THE CAUCASUS: EARTHQUAKE SOURCE MECHANISMS AND RUPTURE HISTORIES OBTAINED FROM INVERSION OF TELESEISMIC BODY WAVEFORMS - Tan O.; Taymaz T. (My University, 2006)
The Eurasia-Arabia continental collision region, including surrounding areas of eastern Turkey, the Caucasus, and the Iranian plateau, is one of Earth's most seismically active and rapidly deforming continental regions. The wide range of deformation processes occurring in this relatively confined region makes the eastern Mediterranean region a unique place in which to improve our understanding of the complexities of continental collision, including strike-slip faulting and crustal extension, as well as the associated seismicity and volcanism. The Arabia-Eurasia continental collision mainly forms fold belts along major thrust faults in southeastern Anatolia and in the Caucasus, while originating major strike-slip faults in eastern Anatolia and northwestern Iran capable of generating major destructive earthquakes. The Arabia plate is moving northerly at a rate of ~18 mm/yr, whereas there is a shortening of 6-10 mm/yr along the Caucasus. However, it is not certain how much of this shortening by seismic activity is due to the insufficient time of observations and the lack of reliable data. In addition, the continental collision in eastern Anatolia and the northward subduction of the Africa plate beneath western Turkey and the Aegean region are causing extension of the continental crust in the overlying Aegean extensional province. Eastern Turkey is experiencing crustal shortening and thickening due to northward motion of the Arabia plate relative to Eurasia. Although the interplay between dynamic effects of the relative motions of adjoining plates controls large-scale crustal deformation and the associated earthquake activity on the major fault zones in the region, a few large earthquakes have occurred since the 1960s, and many great earthquakes have been reported in historical records. The source mechanisms and rupture histories of the earthquakes that occurred in the Caucasus and surrounding regions are estimated from teleseismic long-period and broadband body waveform (P- and SH-waves) data recorded by worldwide seismograph networks. We have studied twenty earthquakes and compiled the other reported twenty-four earthquakes' source parameters to correlate with the regional tectonic process under way. In general, the dip angles of the thrust faulting in the Caucasus are shallow, and the depths of the events are no more than 20 km, which indicates seismogenic thickness. Contrary to previous studies, the sources of the earthquakes in the region do not have complex rupture properties. The north-south seismic deformation in the Lesser and Greater Caucasus was found to be ~1 mm/yr from moment summation of the events. The slip vectors indicate that the northward plate motion changes its direction not only in the Caucasus but also on the Northeast Anatolian fault. © 2006 Geological Society of America.
Keywords: CAUCASUS; EARTHQUAKE SOURCE MECHANISM; EASTERN TURKEY; SEISMOTECTONICS